Dietary Copper Intake and Its Association With Telomere Length: A Population Based Study - Lin, Zhu; Gao, Hongmei; Wang, Bing; Wang, Yongqiang (Frontiers in Endocrinology, 2018)
Background: Telomere is regarded as the fundamental aspect of cellular aging and copper is recognized as one of the most essential trace elements. The role of dietary copper intake in telomere length maintenance is seldom examined. This study aims to investigate if telomere length is to be associated with daily dietary copper intake. Methods: We used epidemiological data from a large national population-based health and nutrition survey. Dietary intake was assessed during the 24–h period before the interview date when blood sample was collected. Telomere length was measured from blood leukocyte using PCR method. The relationship between telomere length and dietary copper intake was assessed using multivariable linear regression models. We also examined if obesity, measured by body mass index, could modify the observed association. Results: There are 7,324 participants had both leukocyte telomere length measured and dietary copper intake assessed, around 48.0% of them were men. Telomere length was longer in women than that in men (1.05 ± 0.26 vs. 1.00 ± 0.26 T/S ratio), while dietary copper intake was less in women than that in men (1.12 ± 0.80 vs. 1.51 ± 1.61 mg). After controlling for age, sex, ethnicity, physical activity, current smoking status, hypertension, cardiovascular diseases, and body mass index in the multivariable linear regression models, one unit increase of log-transformed dietary copper intake was significantly associated with longer telomere length (β = 0.02, 95% confidence interval: 0.01, 0.04). We did not find a significant sex difference for this association. Conclusions: Dietary copper intake was significantly associated telomere length.The role of copper in human health might be involved in biological aging process.